Oscillometric—Volumetric Measurements of Pure Gas Adsorption Equilibria Devoid of the Non-Adsorption of Helium Hypothesis - J.U. Keller; M.U. Göbel (Adsorption Science & Technology)
A new method is presented to measure pure gas-adsorption equilibria on porous solids or powders without using a hypothesis on the void volume of the solid adsorbents, such as the non-adsorption of helium hypothesis. The proposed method involves combined volumetric/manometric and dynamic measurements, namely, observations of the frequency of small adiabatic oscillations of the adsorptive gas in equilibrium with the adsorbed phase or adsorbate. The oscillations of the adsorptive gas are initiated by small oscillations of a sphere or a cylinder positioned in a vertical tube above the vessel containing the gas and adsorbents [reversion of experiment by Rüchardt (1929), Flammersfeld (1972), Keller (2014)]. Experiments show that adsorbates have two different phases consisting, respectively, of molecules which are only weakly bound to adsorbent's atoms so that they can participate in the low-frequency gas oscillations (<10 Hz) and other molecules that are strongly bound to adsorbent's atoms so they are ‘stiff’, that is, cannot participate in the gas oscillations, with eigenfrequencies being in the range of 10 10 –10 12 Hz. The theory of these measurements will be presented and data of adsorption equilibria of He, N 2 , Ar and CO 2 on activated carbon BAX 1100 and zeolite KÖSTROLITH 4ABFK at near ambient conditions will be given and discussed to a certain extent.